Economic and financial crimes and ICT : an appraisal of the response of the Nigerian criminal law - Arowosaiye, Yusuf Ibrahim (Ahmad Ibrahim Kulliyyah of Laws, International Islamic University Malaysia, 2009)
This study focuses on the response of the Nigerian criminal legislations to the contemporary phenomenon of economic and financial crimes and ICT as enabler. The study critically examines the adequacies or otherwise of the existing Nigerian criminal legislations, Shariah Penal Code inclusive, to meet the facets of challenges posed by the prevalence of economic and financial crimes and ICT infrastructures as facilitating tools. The continuous legislative and non-legislative measures undertaken by the past and present Nigerian government in response to the growing trend of this menace are highlighted in the study. Since technology has made national borders more permeable, economic and financial crimes are no longer a local phenomenon but a global problem. Thus, the study employed a methodological evaluation of the common themes and varying national and international perspectives that come into play in response to the phenomenon. This study reveals that the existing Nigerian criminal legislations are grossly inadequate to address the prevailing problem of ICT related economic crimes. The study also reveals that criminalizing economic and financial crimes through legislative means alone would not produce the expected effective response to the menace. This study therefore recommends for vigorous pursuit of both legislative and non-legislative measures to bring the phenomenon to a barest minimum. The study further recommends for necessary amendments to the affected Nigerian legislations which provisions are inadequate to effectively address the subject of economic and financial crimes. It also advocates for immediate passage of the pending Nigerian Cyber Crime Bill 2005 titled “Computer Security and Critical Information Infrastructure Protection Bill 2005”. The Bill if eventually passed into law will serves as Nigerian specific cyber crime law to address electronically perpetrated economic and financial crimes.